KESADARAN GENERASI MUDA DALAM MEWUJUDKAN TINDAKAN ANTI KORUPSI SEBAGAI AGENT PERUBAHAN UNTUK INDONESIA LEBIH MAJU - Alifiyanto Wibowo (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
Generation in realizing anti-corruption actions as agents of change for a more advanced Indonesia, where the role of the younger generation is very influential for the life of the nation for the future with actions starting from an early age where problems related to corruption in Indonesia may still be difficult. to be eliminated among the current generation where corruption has become a very common phenomenon among the people, with the younger generation taking the first steps to form anti-corruption actions based on Pancasila, they can become one of the next generations of the nation who are very anti-corruption and awareness law that remains within each of us, the research method used in writing this article is an empirical research method by collecting data through daily behavior and direct actions among marketed people, by prioritizing the younger generation to changing bad habits to be clean for example clean from ingrained corruption, based on young people who are highly insightful, honest, courageous, critical, caring, optimistic and resilient in the problems that exist in Indonesia, for example corruption.